1998
DOI: 10.1046/j.1365-2141.1998.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Lymphoid’ blast crisis of chronic myeloid leukaemia is associated with distinct clinicohaematological features

Abstract: It has been suggested that in blast crisis (BC) of chronic myeloid leukaemia (CML) the clinical and laboratory features of patients with 'lymphoid' phenotype differ from those of patients with non-lymphoid BC. In order to assess any differences, 97 patients consecutively diagnosed with BC that followed a known chronic phase of CML were analysed. 19 patients had 'lymphoid' BC: in 17 the blasts expressed a B-lineage phenotype: in the remaining two they corresponded to T lymphoblasts. Four cases of B-lineage phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 31 publications
(53 reference statements)
1
17
0
2
Order By: Relevance
“…Furthermore, peripheral eosinophilia and basophilia were also uncommon in the lymphoblastic CML cases. Other studies have shown that lymphoid blast crisis, compared with myeloid, is associated with less frequent splenomegaly, less peripheral basophilia, and a lower frequency of additional clonal abnormalities, and thus are consistent with our findings presented here [14,15]. Furthermore, lymphoid blast crisis is usually associated with a better survival and response to therapy [16].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, peripheral eosinophilia and basophilia were also uncommon in the lymphoblastic CML cases. Other studies have shown that lymphoid blast crisis, compared with myeloid, is associated with less frequent splenomegaly, less peripheral basophilia, and a lower frequency of additional clonal abnormalities, and thus are consistent with our findings presented here [14,15]. Furthermore, lymphoid blast crisis is usually associated with a better survival and response to therapy [16].…”
Section: Discussionsupporting
confidence: 92%
“…6,7 Achieving a long-lasting remission, however, seems unlikely with this approach. As the favourable treatment-response associated with lymphoid BC is brief with a median survival of 9 months after diagnosis, plans for definitive strategies such as allogeneic BMT should be implemented rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Por el contrario, la citometría de flujo es útil para realizar el recuento de blastos y diferenciar entre las fases crónica, acelerada y de crisis blástica, y para determinar el inmunofenotipo de los blastos en la crisis blástica (mieloide en 60% a 70% de los casos versus linfoide en 20% a 30%) (35). No obstante, la reciente introducción de nuevas herramientas técnicas basadas en la utilización de perlas inmunomarcadas para detectar la proteína de fusión del BCR-ABL, abre las puertas, como nueva prueba muy sensible y específica, para confirmar o descartar con gran rapidez la presencia de la t(9;22) en casos en los que existe una sospecha diagnóstica razonada de leucemia mieloide crónica (39) La citometría de flujo también es útil en la detección de mastocitosis sistémica, relacionada con síndromes mieloproliferativos o con neoplasia mieloide de otro tipo, como leucemia mieloide aguda o síndromes mielodisplásicos, al evaluar la expresión del marcador CD117 para la identificación de los mastocitos en su conjunto, que en las mastocitosis presentan de forma aberrante expresión de CD25 y CD2 (36,37).…”
Section: Paneles Inmunofenotípicos Para El Estudio De Síndromes Mielounclassified